Analisis Pengaruh Kualitas Pelayanan, Kelayakan Harga, dan Kualitas Produk terhadap Kinerja Penjualan di Zahra Store Yogyakarta - Fitroh, Wulan Nurul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this research is to determine the influence of service quality, price fairness, and product quality on sales at Zahra Store Yogyakarta. The method used in this research is descriptive quantitative with multiple linear analysis. The population in this research is the customers at Zahra Store Yogyakarta, with a sample size of 100 respondents. The data collection method used a questionnaire. The results of the research conclude that (1) service quality has a positive and significant influence on sales performance, with a coefficient of 0.001, (2) price fairness has a positive and significant influence on sales performance, with a coefficient of 0.017, and (3) product quality has a positive and significant influence on sales performance, with a coefficient of 0.000. Keywords: Service Quality, Price Fairness, Product Quality, Sales Performance.